Sciagawka z angielskiego : czesc 2 wzory zdan cd. - Godziszewska-Pac, Ida. (Warszawa : Proszynski i S-ka, 2000)
A book of examples of grammatical sentences in English for Polish speakers.
Keywords: English language -- Conversation and phrase books -- Polish